Integrasi Pendidikan Karakter dalam Pembelajaran Bahasa Arab di MTsN 2 Sidoarjo - Aisya Aulia; Muhammad Afifudin Dimyathi (Tarling : Journal of Language Education, 2024)
The integration of character values into the learning process has become a major focus for many educational institutions, as it is considered an indicator of success in shaping students' characters. This study uses a descriptive method with a qualitative approach, where the data collected through interviews, observations, and documentation. The data analysis process includes several steps, such as data collection, reduction, presentation, and conclusion drawing. The primary objective of this research is to explore the integration of character education in learning activities in the Arabic language subject at MTsN 2 Sidoarjo. The strategies applied include observing and analyzing teaching materials and teaching methods. The research findings show that character education is integrated through various Arabic language skills, such as listening, speaking, reading, and writing. For instance, the theme "خَالِق الْعَالَم" teaches the importance of gratitude and environmental responsibility, while the theme "جَمَال الطَّبِيْعَة" encourages students to appreciate the beauty of nature. Additionally, teachers use effective teaching methods and create a conducive learning environment. The results of this study indicate that the integration of character education in Arabic language learning not only improves students' language skills but also contributes to forming individuals who are responsible, environmentally conscious, and possess good morals in their daily lives.